Implementation of Scientific Approach in the 2013 Curriculum on History Learning - Permatasari, Eka Aprilia (Indonesian Journal of History Education, 2018)
The District Education Office Trunk designated several schools, including SMA 2, to implement the 2013 curriculum, with this study focusing on two main aspects: the implementation of Curriculum 2013 in teaching history in schools, and the methods used to incorporate a scientific approach to history education. The research aimed to provide comprehensive insights into how the Curriculum 2013 was applied within the educational framework of history classes, examining both the effectiveness and practical aspects of this integration. Specifically, the study sought to understand how the curriculum's principles were translated into teaching practices, evaluating the impact on both teaching methods and student comprehension. Additionally, the research explored the incorporation of a scientific approach to history education, assessing its influence on pedagogical strategies and the depth of student learning. The overarching goal was to evaluate the overall execution and outcomes of these educational strategies, offering a detailed understanding of the curriculum's application and the efficacy of the scientific approach in enhancing history education. Through in-depth analysis, the study aimed to contribute to a broader understanding of the practical challenges and successes in implementing the 2013 curriculum, providing valuable insights for educators and policymakers aiming to improve history education through innovative and scientifically-grounded methods.